Automation cost flexibility and firm value - Ince, Barıs; Iskenderoglu, Cansu (Journal of Corporate Finance, 2025)
This paper documents that industrial robots enhance firms’ ability to reduce operating costs, especially during periods of declining sales. Building on this, we propose a firm-level measure of automation cost flexibility (ACF), which quantifies a firm’s capacity to reduce operating costs through automation. Using this measure, we find that firms with greater ACF exhibit higher firm values. To address endogeneity concerns and strengthen the interpretation of our results, we employ: (i) a difference-in-differences specification with a matching algorithm, and (ii) exploit the 2011 Thailand hard drive crisis as an exogenous shock. The paper further reveals that the positive impact of ACF is more pronounced for firms in highly competitive industries, those facing significant competitive threats, industries with high strategic interactions, and smaller firms. This suggests that cost flexibility encompasses a strategic dimension.